Estimasi Emisi Kendaraan Bermotor dan Tampakan Lumut Kerak untuk Memprediksi Paparan Traffic-Related Air Pollution pada Sekolah Dasar di Kota Kendari - Sumarlin Sumarlin; Wa Ndibale; La Utu; Karmila Sari (Fakultas Teknik, 2021)
Increasing the number of vehicles in Kendari could has the potential to increase TRAP exposure in elementary schools located on the side of the highway. The purpose of this study was to describe the emission load of vehicles, the appearance of lichens and to predict exposure to TRAP in Sekolah Dasar Negeri (SDN) on the side of the highway in Kendari City. This study uses a quantitative approach, survey methods with sampling techniques in three different locations. The results showed that the emission burden of vehicles at SDN 6 Kendari and SDN 25 Kendari was higher, the percentage of lichens present was lower and the appearance was duller than SDN 92 Kendari. This condition can be predicted as an initial indication of a decline in air quality at that location due to periodic exposure to TRAP.